Microcontroller Based Automatic Light Monitoring Implementation Using Sound Sensor - Ovlansisco Lumbantobing (ITScience (Information Technology and Science), 2022)
In this study, a device was designed to be able to control devices with sound waves, a smart home control system allows humans to control their home electrical devices such as lights using only voice commands without the need to move from place to place to turn on or turn off an equipment. When the indoor light user runs the system or turns on the light with sound waves, the sound sensor sends an input signal to the microcontroller which is then processed with the microcontroller output in the form of voltage to turn on the load, the system will function when the FC-04 sound sensor gets sound input (sound code) in the form of claps with a value of 1 then accumulated on the Arduino with a value above 400 millis according to the uploaded program to be used as a 5 volt output to turn on/off the lights.